Gaza’s Subterranean Warfare: Palestinian Resistance Tunnels vs. Israel’s Military Strategy - Majd Abuamer (21841715) (2024)
Actors with limited military capabilities resort to tunnel warfare to counterbalance military and technological disparities with the larger army. From the 1970s onward, tunnels have been used remarkably by non-state actors and liberation movements. Over the last two decades, Israel has set the destruction of the tunnels of the Palestinian armed groups as a primary goal of its massive wars in the Gaza Strip. At the same time, Palestinian armed groups have strategically harnessed the subterranean realm, rendering it an operational tool and developing a tunnel system. This study explores the subterranean warfare in the Palestinian-Israeli conflict, exploring the historical evolution of the Gaza tunnels, their effectiveness, types, and military uses. It also scrutinizes the Israeli military strategy toward these tunnels, examining the techniques employed for detection and destruction of these tunnels, along with their inherent limitations. Other Information Published in: Studies in Conflict & Terrorism License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/1057610x.2024.2347843